Limb-shaking TIA: a case of cerebral hypoperfusion in severe cerebrovascular disease in a young adult - Tom E. Richardson; Paul Beech; Geoffrey C. Cloud (BMC Neurology, 2021)
Abstract Background Limb-shaking transient ischaemic attacks (TIAs) are an under recognised presentation of severe cerebrovascular disease resulting from cerebral hypoperfusion. Patients present with jerking, transitory limb movements precipitated by change in position or exercise that are often confused with seizure. Cerebral perfusion imaging studies are an important tool available to aid diagnosis. Case presentation We present the case of a young female who developed limb-shaking TIA in the context of progressive severe intracranial atherosclerotic disease (ICAD). Previous cortical infarction raised suspicion for seizure as a cause of her symptoms. However, single photon emission CT (SPECT) with CT acetazolamide challenge identified severe left hemisphere cerebral hypoperfusion and a diagnosis of limb-shaking TIA was made. Symptoms improved with maximal medical management. Conclusions This case highlights the importance of cerebral perfusion imaging for diagnostic confirmation as well as therapeutic options available to alleviate symptoms and reduce stroke risk in patients with limb-shaking TIA.